Bacterial surface derived extracellular vesicles: A ground‐breaking approach in cancer therapy - Asmit Das; Swarup Sonar; Ketki Kalele; Vetriselvan Subramaniyan (Wiley, 2024)
Abstract Conventional cancer therapies are often limited by inherent and acquired drug resistance, non‐specific toxicity, and suboptimal drug delivery. Bacterial extracellular vesicles (BEVs), including outer membrane vesicles and membrane vesicles, present a novel therapeutic strategy for cancer treatment. BEVs were found in both Gram‐negative and Gram‐positive bacteria. This article provides a classified investigation of the therapeutic potential of BEVs in cancer treatment. We discuss the molecular mechanisms underlying their observed anti‐tumor effects, including the induction of apoptosis in cancer cells, suppression of angiogenesis within the tumor microenvironment, and stimulation of both innate and adaptive anti‐tumor immune responses. Moreover, BEVs being biocompatible opens avenue for targeted drug delivery systems, potentially improving the therapeutic index of conventional chemotherapeutics. Challenges to clinical translation, such as BEV heterogeneity and potential immunogenicity, are addressed. We also explore future directions for research and development, comprehensively highlighting how BEVs transform the landscape of precision oncology and cancer treatment, eventually improving patient outcomes.